MONTAGE OF A GENRE: INTERSECTIONS OF BIOGRAPHY, DOCUMENTARY AND FICTION IN CELEBRITY DOCUMENTARIES - Antadze-Tamminga, Keti (Online Journal of Humanities ETAGTSU, 2024)
The latest fully authorized documentary, Montage of Heck (2015) by Brett Morgan, delves into the life of Kurt Cobain, presenting a unique form of storytelling that blends documentary and fiction. This film is notable for its emotional truth, which caters to the audience’s yearning for the romanticized image of the deceased idol. Montage of Heck stands out for its innovative integration of multiple genres, creating a distinctly intimate viewing experience by merging biographic, documentary, and fictional elements., This innovative approach, which I term "biographic docufiction," represents a recent trend in celebrity documentaries. Despite its novelty, this subgenre has yet to be extensively examined in scholarly discussions. My analysis will contribute to this field by exploring the characteristics of biographic docufiction, focusing on its unique integration of biographic, documentary, and fictional practices within a single film. Additionally, I will examine how this cross-genre methodology impacts the audience, highlighting the film’s distinctive manner of storytelling and its effects on viewers. My approach focuses on analyzing film elements through the lens of cultural studies, emphasizing its structural and conceptual characteristics as well as the functional roles the film plays within its cultural context. Full Text (PDF)